2018
DOI: 10.1039/c7qi00615b
|View full text |Cite
|
Sign up to set email alerts
|

Chiral metal–organic frameworks constructed from four-fold helical chain SBUs for enantioselective recognition of α-hydroxy/amino acids

Abstract: Three chiral 3D metal–carboxylate frameworks have been successfully synthesized, featuring four-fold helical metal chains as SBUs. Co-MOFs could recognize enantio-selectively α-hydroxy/amino acids by the change of CD signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Both frameworks crystallize in the chiral I 4 1 22 system and are isostructural to the reported (Al, In, Mg, Ni, etc.) MOFs. These frameworks have shown excellent adsorption ability or enantioselective recognition, but proton-conductive properties have not been reported yet. The asymmetry unit of InOF-1 consists of an In­(III) ion, a quarter of BPTC 4– ligand, half of a hydroxide anion.…”
Section: Resultsmentioning
confidence: 99%
“…Both frameworks crystallize in the chiral I 4 1 22 system and are isostructural to the reported (Al, In, Mg, Ni, etc.) MOFs. These frameworks have shown excellent adsorption ability or enantioselective recognition, but proton-conductive properties have not been reported yet. The asymmetry unit of InOF-1 consists of an In­(III) ion, a quarter of BPTC 4– ligand, half of a hydroxide anion.…”
Section: Resultsmentioning
confidence: 99%
“…A small number of studies reported chiral MOF sensors exhibiting initial CD signals, which could be applied for the recognition of specific enantiomers of chiral compounds by analyzing the difference in CD signal intensities. [ 69,70 ] Nonetheless, observation of the intensity variations is not always a precise recognition method, as changes in the local environment of the species may lead to erroneous determination. An appearance of a new peak in the CD sensing would be a more efficient and reliable approach.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing chiral sources to design helical complexes can result in inherent chirality. Also, symmetry breaking with an achiral source can produce a helical structure [ 54 ]. [ZnLBr] was synthesized using a homochiral precursor, N –(4–Pyridylmethyl)- L -leucine·HBr, the aperture size was calculated around 9.8 A°.…”
Section: Mixed Matrix Membranes In Various Combinationsmentioning
confidence: 99%